Motivasi Masyarakat Melakukan Kegiatan Sandboarding Sebagai Sarana Olahraga Rekreasi di Pantai Parangkusumo - Pratomo, Andri Septo (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the study was to determine and describe the motivation of people do sandboarding activities as a means of recreation sports on the beach Parangkusumo Yogyakarta. This study used a qualitative researchmethod, which means to explain the phenomena that occur in the community who do activities sandboardingon sand dunes Parangkusumo Yogyakarta.Pengumpulan data using observation, interviews, questionnairesand documentation. Data analysis used descriptive analysis model according to Miles and Huberman. Basedon the results of research conducted indicates that the motivation of people to carry out activities on the beachsandboarding Parangkusumo Yogyakarta in 2014 fit in either category From the research it can be concludedthat the level of motivation of people to carry out activities on the beach sandboarding ParangkusumoYogyakarta is good, these results certainly cannot be separated from some of the aspects that need support.Suggestion that the author can give is with sandboarding as an alternative recreation, to increase publicawareness of the importance of recreation, but also for the people who are expected to play a more activesandboarding again play so that later sandboarding be recognized by the public